Bay Street Esplanade, Barbados - (:unkn) unknown (My University, 2018)
Street lined with palm trees. Various modes of transportation depicted including buses, bicycles, cars. To the left two persons can be seen sitting on an outside seating accommodation. On the back : Copyright Barbados Publicity Committee, printed in Scotland by Robert MacLehose & Co. Ltd. Glasgow.
Landscape; black and white, 4 x 6 in.
Keywords: Gazebos; Bandstands; Bicycles and tricycles; Automobiles; Buses; Street scene